Avaliação dos teores de metais pesados no solo e na planta de cana-de-açúcar sob adubação com lodo de esgoto e vinhaça - Camilotti, Fábio [UNESP]; Andrioli, Itamar [UNESP]; Marques, Marcos Omir [UNESP]; da Silva, Alysson Roberto; Tasso Júnior, Luiz Carlos (My University, 2009)
The objective of this work was to evaluate Cd, Cr, Ni and Pb total contents in soil and sugar cane after four annual applications of sewage sludge and vinasse to supply all N and all K required by the crop. A field experiment was carried out on clayey Typic Haplustox. It was used a randomized block design with seven treatments and three replications. The treatments consisted in: (i) rate of sewage sludge to supply 100% of the N required by the crop; (ii) rate of sewage sludge to supply 200% of the N required; (iii) rate of vinasse to supply 100% of the K required; (iv) rate of vinasse to supply 200% of the K required; (v) combination of the treatments (i) and (iii); (vi) combination of the treatments (ii) e (iv); (vii) control (mineral fertilization). The contents of Cd, Cr, Ni and Pb in sewage sludge reached maximum values of 1.58, 41.66, 35.17 and 45.25 mg kg-1, respectively. These metals were not detected in vinasse. The residues were applied annually for four years. At the end of this period, sewage sludge and vinasse accumulated rates, that get up to 51 t ha-1 and 762 m3 ha-1, respectively, did not cause alteration in Cd, Cr, Ni and Pb total contents in soil, up to 50 cm of depth, and in plant. Sewage sludge and vinasse application to supply N and K for sugar cane did not offer soil pollution risk by heavy metals.
Evaluation of heavy metals contents in soil and sugarcane plant under fertilization with sewage sludge and vinasse
Keywords: Heavy metals; Organic residues; Pollution; Soil; Sugarcane